Enhancing Motivation in Online Courses with Mobile Communication Tool Support: A Comparative Study - Chaiprasurt, Chantorn; Esichaikul, Vatcharaporn (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
Mobile technologies have helped establish new channels of communication among learners and instructors, potentially providing greater access to course information, and promoting easier access to course activities and learner motivation in online learning environments. The paper compares motivation between groups of learners being taught through an online course based on an e-learning system with and without the support of mobile communication tools, respectively. These tools, which are implemented on a mobile phone, extend the use of the existing Moodle learning management system (LMS) under the guidance of a mobile communication tools framework. This framework is considered to be effective in promoting learner motivation and encouraging interaction between learners and instructors as well as among learner peers in online learning environments. A quasi-experimental research design was used to empirically investigate the influence of these tools on learner motivation using subjective assessment (for attention, relevance, confidence, satisfaction, and social ability) and objective assessment (for disengagement, engagement, and academic performance). The results indicate that the use of the tools was effective in improving learner motivation, especially in terms of the attention and engagement variables. Overall, there were statistically significant differences in subjective motivation, with a higher level achieved by experimental-group learners (supported by the tools) than control-group learners (unsupported by the tools).